Panel unit root tests in the presence of a multifactor error structure - Mohammad Hashem Pesaran; L. Vanessa Smith; Takashi Yamagata (Institute for the Study of Labor (IZA), 2007)
This paper extends the cross sectionally augmented panel unit root test proposed by Pesaran (2007) to the case of a multifactor error structure. The basic idea is to exploit information regarding the unobserved factors that are shared by other time series in addition to the variable under consideration. Importantly, our test procedure only requires specification of the maximum number of factors, in contrast to other panel unit root tests based on principal components that require in addition the estimation of the number of factors as well as the factors themselves. Small sample properties of the proposed test are investigated by Monte Carlo experiments, which suggest that it controls well for size in almost all cases, especially in the presence of serial correlation in the error term, contrary to alternative test statistics. Empirical applications to Fisher's inflation parity and real equity prices across different markets illustrate how the proposed test works in practice.
Keywords: C12; 330; Panel unit root tests; cross section dependence; multi-factor residual structure; Fisher inflation parity; real equity prices; Panel; Unit Root Test; Monte-Carlo-Methode; Faktorenanalyse; Theorie